Navigating Fragmentation: Community Health Interventions For Street-Connected Children Within Health Systems - Projest, Beranard (International Journal of Global Community, 2026)
Street-connected children live at the edges of urban health systems, where poverty, mobility, and stigma quietly shape who receives care and who is left behind. In Tanzania, community-based welfare interventions are often the first, and sometimes only, point of contact with health services for these children. However, how these interventions function in everyday practice remains underexplored. This study examined how community-based welfare initiatives support access to healthcare among street-connected children in Dodoma City, while also tracing the barriers that continue to limit service use. Using a qualitative case study design, in-depth interviews and focus group discussions were conducted with street-connected children and key stakeholders, including community health volunteers, NGO coordinators, and district health and social welfare officers. Thematic analysis revealed that outreach, referral support, case management, and accompaniment to health facilities play a critical bridging role between the street and formal care. Community actors frequently navigate health systems on behalf of children who lack identification, financial means, or adult advocates. Even so, access remains fragile. Direct and indirect costs, provider stigma, loss of insurance cards, and institutional practices that overlook street-connected children repeatedly interrupt care pathways. Many children depend on peer networks or NGO escorts to be acknowledged in clinical spaces. Community-based interventions ease immediate barriers but cannot compensate for fragmented health systems. Strengthening equitable access requires child-sensitive service pathways, reduced administrative obstacles, and integrated medical–social responses grounded in rights-based approaches. Without these shifts, street-connected children will continue to navigate care through improvisation rather than inclusion.